MASS BLOOD SURVEY (MBS) MALARIA DI DESA BANG HAJI WILAYAH KERJA PUSKESMAS SEKAYUN BENGKULU TENGAH - Ida Rahmawati; Dwi Putri Sulistyaningsih; Mika Oktarina; Violita Siska Mutiara (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2020)
Background: Malaria is a major health problem that affects all age groups of individuals that can cause death and disability. Malaria is spread through the bite of a mosquito that has been exposed to a parasitic infection. Only with just one bite, this infection can cause death to a person. Prevention efforts by means of early detection of malaria are expected to be able to suppress mortality and morbidity from malaria. The purpose of this activity is to preventive action by screening or early detection of malaria in the community in Bang Haji Village, the working area of ??the Sekayun Health Center, Central Bengkulu Regency. Methods: malaria Mass Blood Survey (MBS) measurement using Rapid Diagnostic Test (RDT). The target of the Rapid Test examination is the community in the village Bang Haji which is a malaria endemic village in the working area of ??the Puskesmas Sekayun, the examination was carried out at the Village Hall. Result: measurement result using RDT shows that from 215 people who were tested, there was 1 resident who was positive for malaria (0.46%). Conclusion: results screening using MBS malaria measurement using RDT was found to be 1 Plasmodium vivax malaria positive person. Screening conducted on the community in Bang Haji Village, the working area of ??the Sekayun Health Center, is expected to improve vigilance for all parties, because the transmission of malaria occurs very quickly.